Seasonal Dynamics and Production Risk of Hairtail at Sadeng Fishing Port, Indonesia (2019-2024) - Nissa’, Zulfa Nur Auliatun; Dhamira, Aura; Yudinugroho, Maulana; Sari, Ayu Kumala (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study examines the production dynamics and risk level of hairtail at Sadeng Fishing Port from 2019 to 2024. As one of the most economically important commodities, hairtail significantly contributes to local livelihoods, particularly among smallholder fishermen. However, its production is subject to seasonal fluctuations and environmental variabilities. Monthly catch data were analyzed to capture the patterns of hairtail production, while the coefficient of variation was used to measure the production risk. The result shows that the catches peaked typically during January-March, with the highest production occurring in January 2023, and a complete absence of production was recorded in August during multiple years. The production risk shows a slightly negative trend, though the slope is minimal. The value notably fluctuates with higher levels of risk, which coincidentally happen in years influenced by climatic anomalies such as El Niño and La Niña. These findings suggest that both environmental and human-related factors jointly shape the variability of hairtail production. Understanding these dynamics is crucial to reducing the vulnerability of fishing communities and enhancing resilience under conditions of climate uncertainty.